Spontaneous combustion liability between coal seams: A thermogravimetric study - Onifade, Moshood; Genc, Bekir; Bada, Samson (International journal of mining science and technology, 2020)
The spontaneous combustion liability of coal can be determined by using different experimental techniques. These techniques are well-known in their application, but no certain test method has become a standard to prove the reliability of all of them. A general characterisation which included proximate and ultimate analyses, petrographic properties and spontaneous combustion tests (thermogravimetric analysis (TGA) and the Wits-Ehac tests) were conducted on fourteen coal and four coal-shale samples. The spontaneous combustion liability of these samples collected between coal seams (above and below) were predicted using the TGA and the Wits-Ehac tests. Six different heating rates (3, 6, 9, 15, 20 and 25 °C/min) were selected based on the deviation coefficient to obtain different derivative slopes and a liability index termed the TGspc index. This study found that coal and coal-shale undergo spontaneous combustion between coal seams when exposed to oxygen in the air. Their intrinsic properties and proneness towards spontaneous combustion differ considerably from one seam to the other. The Wits-Ehac test results agreed with the TGspc results to a certain extent and revealed the incidents of spontaneous combustion in the coal mines.